First and Last Impressions : A Critical Discourse Analysis of the 2024 Harris vs. Trump Presidential Debate - Leppänen, Minka (My University, 2025)
In this thesis I study what language strategies Kamala Harris and Donald Trump used to project authority during their entrances to the stage and in their closing statements in the presidential debate on September 10, 2024. Using Norman Fairclough’s three-dimensional model I not only pin pointed the language strategies but also tied them to a larger social context to answer the question of how these strategies reflect and reinforce societal norms and power dynamics. My main focus in the entrances was on the non-verbal aspects and in the closing statements I opted to examine the pronoun use of the candidates, partly incorporating Teun A. van Dijk’s Us/Them assessment. To tie these strategies to a larger social context I used a selection of post-debate news articles. My results indicate that while there were some similarities in how the candidates portrayed themselves as leaders, Harris’ leadership persona can be seen as unorthodox for a woman in the sense that she is someone with agentic characteristics, something that is usually expected from male leaders. This is evident in both her language strategies as well as in the media coverage. In terms of pronoun use, it is evident that Harris leaned more to her personal qualifications, whereas Trump did not highlight his own accomplishments but instead wanted to paint the opposition as the enemy. The media portrayed Harris as the winner of the debate, but it is clear from the election results that being well-spoken or winning the debate is not enough. Thus, there are clear indications that Harris losing the election could be tied to her gender.
Keywords: CDA, critical discourse analysis, politics, presidential debates, Kamala Harris, Donald Trump